THE ROLE OF THE PATRIOTIC ACT "MANGILIK EL" IN TEACHING PHYSICS - V.N. В.Н.; Medeshova А.Б.; Zhumabaeva Ж.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The article discusses one of the urgent problems of modern pedagogy - methods of spiritual development of a person. The authors adhere to the point of view, formed in the traditional education system, that upbringing of a person always goes along with learning process. The ways of introducing national values in the study of school subjects are described. The authors investigated the methodological approaches of introducing the program “Looking into the Future: Modernization of Public Consciousness” and the patriotic act “Mangilik El” in teaching a physics course, which includes the comprehensive upbringing of a person who respects the history and culture of his motherland. Methodical recommendations for planning and teaching physics with values of “Mangilik el” are also given.